Interactions between a submerged water jet and a free surface - Kwek, Darren Yi Wei (Nanyang Technological University, 2022)
This Final Year Project investigated the interactions between a submerged water jet and a free surface, with the aim of visualising and analysing the flow behaviour of the jet both below and as it approaches the interface between air and water. CFD simulations of an underwater submerged jet with flow velocity of 0.48 m/s were performed using the VOF multiphase model, together with the realisable − turbulence model. The segregated pressure-based solver, together with the PISO pressure-velocity coupling and explicit volume fraction formulation were chosen as the solver methods in the simulations. A single-phase steady state simulation was first performed as a coarse mesh study, to get an initial understanding of the flow in the absence of a free surface. Subsequently, a mesh dependency study was conducted comprising of a coarse, mid-range and fine mesh with cell counts of approximately three, six and ten million respectively. For the transient investigation, only the fine mesh was used and the simulation was run up to a flow time of two seconds. Results from the study showed that free surface deformation was present as the jet propagates downstream, and although the jet boundary shifts toward the surface, the location of maximum velocity remained at the jet centreline.